We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
158
2
avatar

1.

2

3.

 Mar 19, 2018
 #1
avatar+100439 
+2

Here's the first two

 

1.  Avg Rate of Change

 

f(9)  - f(5)            14 - (-2)             16

_______    =     _______   =        __       =      4

  9  -  5                 9 -   5                4

 

2.   (f/g)x   =  [ 4x^2 + 6x]  /  [ 2x^2 + 13x + 15 ]  =  [ 2x (2x + 3)] / [ (2x + 3) (x + 5)]  =

 

2x / (x + 5)

 

 

cool cool cool

 Mar 19, 2018
 #2
avatar
+1

3.)

 

 

x^2 - 6x + 8 = x-2

x^2 - 7x -6 = 0

(x-7)(x+1) = 0

x = 7 or -1 

 Mar 19, 2018

5 Online Users